(untitled) (Journal of Science and Technology, 2016)
Ageing has become cm industrial practice forte int-pavement plasticity of clays and bodies both in the sherry plastic states but no proper explanation exits. Experiments were conducted on Aged and flora chow re determine whether chemical bald; were Mahar at all. Results of ray diffraction, Infra-red spectroscopy, Differential thermal analysis (D. TA) indicate that ageing affects both the mineralogical and structural aspects of clays. h is there-fore wry likely that ageing is more of a physical phenomenon than chemical activity.